2018
DOI: 10.19177/rgsa.v7e32018624-639
|View full text |Cite
|
Sign up to set email alerts
|

Análise Físico-Química E Microbiológica De Águas De Poços Artesianos De Uso Independente

Abstract: O consumo de água subterrânea é uma prática que vem sendo difundida largamente entre a população humana. Para assegurar o uso sustentável e seguro destas águas para consumo é essencial à avaliação da qualidade de água, que está diretamente ligada a questões de saúde pública e ambiental. O objetivo do presente trabalho foi analisar a qualidade da água de poços artesianos utilizadas para o consumo humano no município de Timbiras-MA. Foram avaliados 10 poços a partir de parâmetros físico-químicos e microbiológico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Oliveira et al (2018), performing physical-chemical and microbiological analysis of water from artesian wells for independent use, found results for the physical chemical parameters color and turbidity within the stipulated by the legislation and for the values for the hydrogen potential pH in disagreement with the legislation. Regarding the microbiological result of Oliveira et al (2018), found 70% of the samples were collected without disagreement with the recommendations of Consolidation Ordinance No. 5, of September 28, 2017.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Oliveira et al (2018), performing physical-chemical and microbiological analysis of water from artesian wells for independent use, found results for the physical chemical parameters color and turbidity within the stipulated by the legislation and for the values for the hydrogen potential pH in disagreement with the legislation. Regarding the microbiological result of Oliveira et al (2018), found 70% of the samples were collected without disagreement with the recommendations of Consolidation Ordinance No. 5, of September 28, 2017.…”
Section: Resultsmentioning
confidence: 95%
“…Alves et al (2018), researching the behavior of the specific mass of pineapple pulps as a function of temperature, found the values of the specific masses of pineapple pulps ranging from 1060.31 to 3 1044.32 kg/m at temperatures of 10 to 50 °C. Oliveira et al (2018) observed during studies on pineapple pulp that the specific mass tended to decrease when there was an increase in temperature in their experiment. According to Mercali et al (2011), Diniz et al (2014 and Alves et al (2018), the specific mass values of pineapple and watermelon pulps decrease with increasing temperature, probably due to the volumetric expansion of the fluid caused by the reduction of the intermolecular force connection.…”
Section: Determination Of the Volumetric Expansion Coefficient Of Pineapple And Watermelon Pulpsmentioning
confidence: 95%
“…However, the pH was below the recommended lower limit in all wells, presenting values between 5.02 and 5.92 (Table 2). The pH of well waters are often below 6.0 in different localities in the state of Maranhão, such as in Raposa, São Luís, Timbiras, Paço Lumiar, Santa Helena and Itapecuru-Mirim, and in Santa Helena a pH of 3.8 was observed (Alves, 2010;Coelho et al, 2017;de Oliveira et al, 2019;Marques et al, 2010;Oliveira, 2018;Rodrigues et al, 2020). In the rural area of Imperatriz, an artesian well with pH 6.0 was found, which is at the lower limit of the reference value (Santos et al, 2020).…”
Section: Resultsmentioning
confidence: 99%